O impacto da Revolução Russa no movimento anarquista uruguaio (1917-1921) - George Fellipe Zeidan Vilela Araújo (2012)
In the course of the international labor movement, the Russian Revolution of 1917 is one of the moments of greatest importance, often cited as a watershed for the Left all over the world included not only socialism and communism but also the anarchism. Although geographically far away, the echoes of the Russian Revolution were also felt in Latin America, a region that was also going through agitated moments. In many Latin American countries such as Uruguay, a nascentsocial-labor movement was questioning the social order that had been imposed by the elites since the end of the colonial period. The major tendency in the Uruguayan social-labor movement was the anarchist, and although the Revolution stirred excitement and optimism, it has given rise to numerous ideological and conceptual questions. If at first, virtually all libertarian groups welcomed it and expressed their solidarity, later, many expressed their distrust and later rejection of Soviet Russia. However, some groups, in frank contradiction with the anarchists ideas, not only continued to defend the revolution, the dictatorship of the proletariat and the Bolshevik government, but also have led to an ideological polemic with the groups that were opposed to it. Two main trends began to form: the one based on the La Batalla journal, and the one represented by the journal El Hombre. The clash between them would be largely responsible for subsequent split of the Federación Obrera Regional Uruguaya (F.O.R.U.) and decline of Uruguayan anarchism.